RAZING HEIGHT OF XARAÉS GRASS IMPROVE LONGISSIMUS MUSCLE FATTY ACIDS PROFILE OF NELLORE CATTLE - Lala, Bruno Lala; Cecato, Ulysses; Pereira, Vinicius; Mari, Gracielle; Grande, Paula; Müller, Leonardo; Silva, Stefania Claudino; Bridi, Ana Maria (Revista Valore, 2019)
Differences in chemical composition and fatty acid profile of Longissimus muscle in Nellore cattle under different grazing heights (15, 30, 45 and 60 cm) of xaraés grass were tested. Longissimus muscle sample was collected 24 h after slaughter and the chemical (moisture, mineral residue, protein and total lipids) and fatty acids composition was quantified. Only fatty acid profiles were different on percentages of lauric (12:0), oleic (18:1n9c) and eicosadienoic acid (20:2), being best in height of 30 cm grazing (0.36%, 0.85% 39.7% and 1.83%, respectively); myristic (14:0) and conjugated linoleic acid (C18:2,c9-t11) presented better value for the height of 60 cm (4.04% and 0.23%, respectively). Percentage of omega-3 (n-3) and omega-6 (n-6) were better at 30 cm grazing, with values of 2.61% and 8.32%, respectively. Grazing height between 30 and 45 cm improves the levels of fatty acids, important to human healthy, in Longissimus muscle of Nellore cattle.